Discovery and development of a safe and efficient COVID-19 mRNA vaccine, STP2104, using a novel capping library screening method - Choi, Kanghyun; Lee, Joo-Young; Kim, Uk-Il; Park, So-Hyun; Hong, So-Hee; Bang, Yoo-Jin; Hwang, Yun-Ho; Lee, Jong-Eun; Park, Suhyun; Kim, Soochong; Lee, Sunhee; Yun, Ye-Jin; et al. (Frontiers in Immunology, 2025)
Messenger RNA (mRNA) vaccines represent a critical avenue for coronavirus disease 2019 (COVID-19) prevention. We developed a COVID-19 mRNA vaccine encoding a codon-optimized full-length ancestral spike (S) protein with a signal peptide, which employs our novel patented co-transcriptional 5′-capping reagent, SmartCap®. From the screening capping library of SmartCap®, an SC101 cap was selected to derive a novel mRNA vaccine, STP2104. An in vitro study of STP2104 incorporating SC101 revealed enhanced protein expression in both the cell lysate and culture medium, and an in vivo immunogenicity study revealed strong humoral and cell-mediated immune responses. STP2104 further displayed potent neutralizing activity in immunized mice as derived via the PRNT50 assay using the wild-type virus. We evaluated the protection efficacy of STP2104 using human ACE2 transgenic mice immunized and challenged with SARS-CoV-2 to acquire the survival rate, virus titration, and histopathology study data. These studies proved that STP2104 is potent enough to induce protective immunity. A novel capping library screening (CLS) method was successfully utilized for exploring the optimal 5′-cap reagent, which improves S gene expression with mRNA stability. The clinical phase 1 studies of STP2104 will prove its safety, tolerability, and immunogenicity as well as the safety of the novel 5′-cap analogue SC101 in humans.